PULLED`UP BY THEIR BOOT STRAPS: A HISTORICAL ACCOUNT OF HOW MUSLIMSI N SOUTH-WEST NIGERIA FARED IN COLONIAL NIGERIA - NWACHUKWU JOHN UZOMA (International Studies Journal)
Islam and Christianity, though not indigenous to Nigeria, are the two major religions in the country. Their paths crossed in the colonial period. The study examines what happened in South West Nigeria when the paths of the two religions crossed in the colonial period. The ambivalence of the British colonial officers, which made them promote Islam in the North and stifle it in the South-West, aroused the curiosity of the writer. Using historical and descriptive methods and relying on primary and secondary sources, it was found that if not for the measures taken by South-West Muslims, Islam could have been eclipsed by Christianity in the area. The paper concludes that Islam was deep-rooted in the South-west region. As a result, it produced dyed-in-the-wool Muslim faithfuls, which is why they did not lose focus despite all that the Christian missionaries and British colonial officials did.